Comparison of Propofol and Midazolam for Sedation in Intensive Care Unit - Amjad, Muhammad Ammar; ., Abdullah; Saeed, Muhammad; Majid Waseem, Syed; Ali Abbas, Muhammad; Ali, Muhammad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the relative efficacy and extubation time by using Propofol and Midazolam for patients requiring sedation in intensive care unit. Study Design: Quasi experimental study. Place and Duration of Study: Intensive Care Unit, Department of Anesthesia, Combined Military Hospital Multan, Pakistan from Jan to Jul 2023. Methodology: Sixty-two (n=62) patients fulfilling the inclusion criteria were incorporated in the study, the were divided in two group of 31 each. Group-P was infused Propofol at the dosage of 0.05mg/kg/min whereas Group-M received Midazolam as 0.1mg/kg/hour. Standard monitoring was used in both groups. End points included efficacy of sedation (RASS +1 to -2), time taken for extubation after stoppage of sedative drugs. Results: Patients in both the groups were comparable in terms of mean age in years 45.17±14.42 and 44.40±13.56 with p value 0.83. Mean time in minutes taken for extubation was 80.40±21.35 and 92.23±22.61 (p-0.042) for Propofol and Midazolam group respectively. Richmond agitation sedation score (RASS) scores of 90% (n=27 patients) and 73.3% (n=22 patients) of the patients remained in desired limits in Propofol and Midazolam groups respectively. Conclusion: Propofol and Midazolam demonstrated efficacy in sedating ICU patients and different profiles regarding safety. The choice of sedative to be individualized, considering the patient’s clinical status and the desired sedation goals.